Efficiency and stock returns: evidence from the insurance industry - Chrysovalantis Gaganis; Iftekhar Hasan; Fotios Pasiouras (Bank of Finland, 2013)
This study investigates whether the capital market values the efficiency of firms. After tracing stock returns and efficiency changes of 399 listed insurance firms in 52 countries during the 2002-2008 period, the paper reports a positive and statistically significant relationship between profit efficiency change and market adjusted stock returns. However, there is no robust evidence that cost efficiency change is associated with stock returns.
URN:NBN:fi:bof-20140807254
Keywords: C22; C34; G22; 330; Efficiency; insurance; stock returns